PENGARUH STRUKTUR AKTIVA, TINGKAT LIKUIDITAS, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - SETIAWATI, LUSI (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The capital structure is the comparison between the use of debt or equity. Under optimal conditions, we have to consider everything that has influence over it. This study aims to obtain empirical evidence about the effect of asset structure, liquidity, firm size, and profitability on capital structure using financial statement data used is a manufacturing company listed on the Indonesia Stock Exchange (IDX) during the years 2009-2011. The population in this study amounted to 144 manufacturing companies listed on the Indonesia Stock Exchange. Samples were taken by purposive sampling method by 30 manufacturing companies that meet multiple criteria. The model used is a regression analysis of panel data. The results showed that the level of liquidity and profitability have a significant effect on capital structure. While the assets structure and firm size had no significant effect on capital structure.